Biomimetic Spider‐Web‐Like Composites for Enhanced Rate Capability and Cycle Life of Lithium Ion Battery Anodes. Issue 17 (2nd May 2017) - Bhattacharya, Pallab; Kota, Manikantan; Suh, Dong Hoon; Roh, Kwang Chul; Park, Ho Seok
Abstract : It is crucial to control the structure and composition of composite anode materials to enhance the cell performance of such anode materials for lithium ion batteries. Herein, a biomimetic strategy is demonstrated for the design of high performance anode materials, inspired by the structural characteristics and working principles of sticky spider‐webs. Hierarchically porous, sticky, spider‐web‐like multiwall carbon nanotube (MWCNT) networks are prepared through a process involving ozonation, ice‐templating assembly, and thermal treatment, thereby integrating the networks with γ‐Fe2 O3 particles. The spider‐web‐like MWCNT/γ‐Fe2 O3 composite network not only traps the active γ‐Fe2 O3 materials tightly but also provides fast charge transport through the 3D internetworked pathways and the mechanical integrity. Consequently, the composite web shows a high capacity of ≈822 mA h g −1 at 0.05 A g −1, fast rate capability with ≈72.3% retention at rates from 0.05 to 1 A g −1, and excellent cycling stability of >88% capacity retention after 310 cycles with a Coulombic efficiency >99%. These remarkable electrochemical performances are attributed to the complementarity of the 3D spider‐web‐like structure with the strong attachment of γ‐Fe2 O3 particles on the sticky surface. This synthetic strategy offers an environmentally safe, simple, and cost‐effective avenue for the biomimetic design of high performance energy storage materials. Abstract : A biomimetic strategy for the design of high performance anode materials, where the structural characteristics and working principles are inspired by sticky spider‐webs, is presented. The spider‐web‐like network traps the active materials tightly, provides high electronic conductivity through a 3D internetworked pathways, and exhibits strong mechanical integrity for enhanced rate capability and cycle life of lithium ion battery anodes.